Preparation method of carbon nanotube composite film applied to extreme conditions

By growing a non-metallic cladding layer on the carbon nanotubes and further growing a nano-scale metal or metal compound cladding layer, the problem of insufficient performance of carbon nanotubes in extreme environments is solved, and the effect of improving its plasma and heat emission resistance is achieved, making it suitable for extreme environments.

CN120158812APending Publication Date: 2025-06-17INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510204389.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-06-17

AI Technical Summary

Technical Problem

Carbon nanotubes have poor oxidation resistance, poor thermal shock resistance and poor plasma etching resistance in extreme environments, which limits their application range.

Method used

The non-metallic cladding layer is grown on carbon nanotubes by chemical vapor deposition, reducing its curvature, and controlling the growth of nano-scale metal or metal compound cladding layers on the basis of it, improving the plasma and thermal emission resistance of the film.

Benefits of technology

Without affecting the mechanical and light transmittance properties of carbon nanotubes, the properties of carbon nanotube films are significantly improved, such as oxidation resistance, plasma resistance, high temperature oxidation resistance, acid and alkali corrosion resistance, and cold and hot impact resistance, making them suitable for extreme service environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120158812A_ABST
    Figure CN120158812A_ABST
Patent Text Reader

Abstract

The invention relates to the field of controllable preparation and application of nanocarbon composite materials, in particular to a preparation method of a carbon nanotube composite film applied to extreme conditions. The method comprises the following steps: by taking a self-supporting film (with the thickness of 10-200nm) formed by overlapping a carbon nanotube network as a base material, controllably depositing a coating layer with the thickness of 0.3-10nm on carbon nanotubes and tube bundles of the carbon nanotubes by adopting physical / chemical vapor deposition and other methods; wherein the coating layer at least contains two of the following elements: B, C, N, O, P, Si, Ge, As, Sb, Bi, Ti, Al, Zr, Mo, W, Ru, Nb, Hf, Re, Rh and the like, and at least one layer is hexagonal boron nitride / cubic boron nitride / boron carbide with high crystallinity; the composite film has excellent physical and chemical properties such as airflow impact resistance, atomic hydrogen / oxygen resistance, hydrogen / oxygen plasma resistance, heat impact resistance, high-temperature oxidation reduction resistance, acid and alkali corrosion resistance and the like on the premise of keeping the properties such as light transmission and flexibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of controllable preparation and application of nano-carbon composites, and specifically to a preparation method for carbon nanotube composite films applied under extreme conditions. By using physical / chemical vapor deposition method, an ultrathin coating layer with high chemical stability can be controllably prepared on carbon nanotube bundles, so as to improve the antioxidant, plasma-resistant, acid and alkali-resistant, and thermal shock-resistant properties of the film while not affecting the excellent mechanical and light-transmitting properties of carbon nanotubes, enabling it to be used in extreme service environments such as strong irradiation, high-temperature oxygen-containing, and high-concentration plasma. Background Art

[0002] Carbon nanotubes composed of sp 2 hybrid carbon atoms have excellent properties such as high thermal conductivity, high electrical conductivity, high elastic modulus, and high strength. The films constructed by carbon nanotubes inherit their intrinsic excellent properties and have broad application prospects in flexible displays, nanoelectronic devices, photoelectric detection, particle protection, etc. However, the disadvantages of carbon nanotubes such as poor high-temperature oxidation resistance, poor heat shock resistance, and poor plasma etching resistance limit their application in extreme service environments.

[0003] To improve the stability of carbon nanotubes in extreme environments, coating a protective layer with higher chemical stability on the surface of carbon nanotubes is a common method. Researchers have developed methods such as liquid-phase coating and vapor deposition to introduce a protective layer on the surface of carbon nanotubes. However, most coating methods make the carbon nanotube film unable to maintain its intrinsic self-supporting structure. This is mainly due to: (1) when treating the carbon nanotube film in liquid phase, the carbon nanotubes and their bundles agglomerate and collapse, becoming dense and uneven; (2) carbon nanotubes have a very high curvature, and other materials cannot be controllably grown on their surface without surface treatment; (3) surface treatment of carbon nanotubes will introduce defects, causing structural damage to the carbon nanotubes and affecting the mechanical properties of the film; (4) the thickness of the coating layer on the surface of carbon nanotubes is uncontrollable, and an overly thick coating layer will seriously reduce the light transmittance and mechanical properties of the film. Summary of the Invention

[0004] The purpose of the present invention is to provide a preparation method for carbon nanotube composite films applied under extreme conditions. To overcome the problem of difficult nucleation on high-curvature carbon nanotubes, first, a non-metallic coating layer is heteroepitaxially grown on carbon nanotubes and their bundles by chemical vapor deposition. The non-metallic coating layer can ensure the structural integrity of carbon nanotubes while reducing the curvature of the tubular structure. Then, a metal or metal compound with a nanoscale thickness is continuously and controllably grown on the basis of the non-metallic coating layer to improve the plasma resistance and thermal emission performance of the carbon nanotube film. Without affecting the intrinsic structure of carbon nanotubes, the thickness of the coating layer is controlled to be less than 10 nm to ensure the light transmittance and mechanical properties of the carbon nanotube film, and a carbon nanotube composite film applicable to extreme environments is obtained.

[0005] The technical solution of the present invention is as follows:

[0006] A preparation method of a carbon nanotube composite film applied to extreme conditions, using a self-supporting film with a thickness of 10 - 200 nm formed by the network lap of carbon nanotubes as the substrate. First, a non-metallic coating layer with a thickness of 0.3 - 10 nm and containing at least two elements among B, C, N, O, P, Si, Ge, As, and Sb is heteroepitaxially grown on the carbon nanotubes and their bundles by atmospheric pressure or vacuum chemical deposition. Then, a metal / alloy or metal compound containing at least one element among Bi, Ti, Al, Zr, Mo, W, Ru, Nb, Hf, Re, and Rh is controllably deposited on the carbon nanotubes and their bundles by physical deposition method; while maintaining the light transmission and flexibility properties, the composite film simultaneously has excellent resistance to gas flow impact, atomic hydrogen / oxygen, hydrogen / oxygen plasma, thermal shock, high-temperature oxidation-reduction, and acid-base corrosion resistance.

[0007] For the preparation method of the carbon nanotube composite film applied to extreme conditions, to improve the thermal shock resistance of the composite film, after depositing the non-metallic coating layer, a metal / alloy or metal compound containing at least one element among Bi, Ti, Al, Zr, Mo, W, Ru, Nb, Hf, Re, and Rh is controllably coated again by a controllable physical deposition method, and the metal compound is a metal silicide, metal nitride, or metal carbide.

[0008] For the preparation method of the carbon nanotube composite film applied to extreme conditions, to improve the plasma resistance, atomic hydrogen / oxygen resistance, or acid-base corrosion resistance of the composite film, the outermost layer of the composite film is h-BN or a metal compound.

[0009] For the preparation method of the carbon nanotube composite film applied to extreme conditions, to improve the high-temperature oxidation-reduction resistance of the composite film, the outermost layer of the composite film is an h-BN, diamond, c-BN, Si3N4, or SiC ceramic material.

[0010] For the preparation method of the carbon nanotube composite film applied to extreme conditions, to maintain the light transmission and mechanical properties of the composite film, the total thickness of the non-metallic coating layer needs to be less than 10 nm; when depositing the coating metal, alloy, or metal compound, the physical deposition method used is atomic layer deposition, magnetron sputtering, ion beam sputtering, or thermal evaporation, which has high controllability of the coating layer thickness, and the deposition thickness is 1 - 5 nm.

[0011] For the preparation method of the carbon nanotube composite film applied to extreme conditions, when the composite film is composed of a single single-walled carbon nanotube, the innermost coating layer should be h-BN, c-BN, or B4C with high crystallinity and high chemical stability, and has a good layered structure and interface quality.

[0012] The described preparation method for carbon nanotube composite films under extreme conditions significantly improves the chemical stability of carbon nanotube films and broadens the application scenarios of carbon nanotubes to extreme service environments such as high-concentration atomic oxygen / hydrogen, high-concentration plasma, strong light irradiation, high-temperature oxygen / hydrogen, high-concentration acid-base, strong air flow impact, or rapid temperature rise and fall.

[0013] The design concept of the present invention:

[0014] The present invention provides a carbon nanotube composite film and an efficient and controllable preparation method thereof that can be used under extreme conditions. First, a non-metal coating layer with a high lattice match is heteroepitaxially grown on the surface of carbon nanotubes and their bundles by heteroepitaxy method. After the coating layer reduces the curvature of the carbon nanotubes, a metal or metal compound coating layer is controllably introduced; the total thickness of the coating layer is controlled within sub-ten nanometers by an accurately controllable physical / chemical vapor deposition method, improving its plasma resistance, high-temperature oxidation resistance, atomic hydrogen / oxygen resistance, acid-base corrosion resistance, thermal shock resistance, etc. while maintaining the light transmittance and mechanical properties of the film; thereby broadening the application scenarios of carbon nanotube films.

[0015] The present invention uses a carbon nanotube film with a thickness of sub-hundred nanometers as the substrate, and controllably coats the carbon nanotubes and their bundles by chemical vapor deposition heteroepitaxy to reduce the curvature of the carbon nanotubes and their surfaces and reduce the barrier of physical deposition coating. Then, a metal or metal compound with a thickness within ten nanometers is further coated by accurately controllable physical deposition, thereby improving the plasma resistance, high-temperature oxidation resistance, and atomic hydrogen / oxygen resistance of the carbon nanotube film. Its advantages are as follows:

[0016] (1) The preparation method of the present invention has strong controllability, can realize the controllable coating of different components (non-metal / metal alloy / metal-non-metal compound) on carbon nanotubes and their bundles, and design coating layers with different chemical compositions according to different extreme application scenarios;

[0017] (2) The preparation method of the present invention can reduce the curvature of carbon nanotubes through heteroepitaxial growth to achieve thin-layer coating, and can control the coating layer thickness to be less than ten nanometers without affecting the light transmittance and mechanical properties of the carbon nanotube film;

[0018] (3) The carbon nanotube composite film obtained by the present invention can improve its plasma / atomic hydrogen oxygen / high-temperature oxidation resistance and other properties, and broaden its application scenarios to extreme conditions. Description of the drawings

[0019] Figure 1 . Optical photograph of single-walled carbon nanotube@h-BN composite film.

[0020] Figure 2. Raman spectra of the original single-walled carbon nanotube film and the single-walled carbon nanotube@h-BN composite film. Among them, the abscissa Ramanshift represents the Raman shift (cm -1 ), and the ordinate Intensity represents the relative intensity (a.u.).

[0021] Figure 3 . Transmission electron microscope images of the single-walled carbon nanotube@h-BN composite film.

[0022] Figure 4 . Transmission electron microscope images of the single-walled carbon nanotube@h-BN composite film after hydrogen plasma treatment.

[0023] Figure 5 . Transmission electron microscope images of the single-walled carbon nanotube@h-BN@Si composite film.

[0024] Figure 6 . Transmission electron microscope images of the single-walled carbon nanotube@Si@h-BN composite film.

[0025] Figure 7 . Transmission electron microscope images of the single-walled carbon nanotube@h-BN@W composite film. Detailed implementation manners

[0026] In order to make the objectives, technical solutions, and advantages of the present invention clearer, the present invention will be described in detail below through examples and the accompanying drawings, but this is not intended to limit the protection scope of this application.

[0027] Example 1.

[0028] In this example, the process for controllably preparing the single-walled carbon nanotube@h-BN composite film is as follows:

[0029] (1) Preparation of the single-walled carbon nanotube@h-BN composite film by low-pressure chemical vapor deposition

[0030] The single-walled carbon nanotube film collected on the cellulose filter membrane was pressed and transferred onto the alumina frame to form a self-supporting network single-walled carbon nanotube film with a thickness of about 50 nm and a light transmittance of 90% for 550 nm visible light. The single-walled carbon nanotube film was placed in a low-pressure chemical vapor deposition system, and ammonia borane was used as the precursor source. When the vacuum degree was 10 - 2 Pa, it was grown at 1000 °C for 90 min.

[0031] (2) Structural characterization of the single-walled carbon nanotube@h-BN composite film

[0032] As Figure 1As shown, from the optical photograph of the single-walled carbon nanotube @ h-BN composite film, it can be seen that its transmittance to visible light at 550 nm after coating with h-BN is 89.8%. The results of Raman spectroscopy characterization show that ( Figure 2 ), the crystallinity of the carbon nanotubes did not change after coating. The composite film was pressed onto a copper mesh microgrid for transmission electron microscopy observation, and the results are as Figure 3 shown. The single-walled carbon nanotube bundles were uniformly coated with h-BN with 6 - 7 layers, and the thickness of the h-BN coating layer was about 2 nm.

[0033] (3) Properties of the single-walled carbon nanotube @ h-BN composite film

[0034] The composite film was placed in air and heated at 500 °C for 24 h, and its structure remained unchanged, indicating that the composite film has excellent high-temperature oxidation resistance. Another composite film prepared under the same conditions was placed in a plasma cleaning equipment, with the power set at 50 W, using hydrogen as the plasma source, and treated at 1×10 -3 Pa (vacuum degree) for 60 min. The composite film still maintained a complete self-supporting structure, and the transmission electron microscopy observation results showed that the microstructures of the carbon nanotubes and h-BN were not damaged ( Figure 4 ). This proves that the single-walled carbon nanotube @ h-BN composite film has excellent plasma etching resistance.

[0035] Example 2.

[0036] In this example, the process for controllably preparing the single-walled carbon nanotube @ h-BN @ Si composite film is as follows:

[0037] (1) Preparation of the single-walled carbon nanotube @ h-BN composite film by low-pressure chemical vapor deposition

[0038] The single-walled carbon nanotube film was prepared in the same manner as in step (1) of Example 1. The film was placed in a low-pressure chemical vapor deposition system, using ammonia borane as the precursor source, and grown at 1000 °C for 60 min when the vacuum degree was 10 -2 Pa.

[0039] (2) Preparation of the single-walled carbon nanotube @ h-BN @ Si composite film by magnetron sputtering

[0040] The single-walled carbon nanotube @ h-BN composite film prepared in step (1) of Example 2 was fixed on the sample stage of the magnetron sputtering equipment. The sample stage was sent into a cavity with a vacuum degree of 1.3×10 -4 Pa, and the sputtering parameters of the magnetron sputtering were set as follows: the starting power was 25 W, the rotation speed of the sample stage was 10 rad / min, the working pressure of the Ar gas was 5 mTorr, the sputtering power was 25 W, the pre-sputtering time was 100 s, and the sputtering time was 600 s.

[0041] (3) Structural Characterization of Single-Walled Carbon Nanotube @ h-BN @ Si Composite Film

[0042] The transmittance of the single-walled carbon nanotube @ h-BN @ Si composite film to visible light at 550 nm was measured to be 89.7%. Then, the prepared single-walled carbon nanotube @ h-BN @ Si composite film was pressed onto a copper mesh microgrid for transmission electron microscopy observation. The results are as follows Figure 5 shown. The single-walled carbon nanotube bundles were not only uniformly coated with h-BN with 6 - 7 layers, and the thickness of the h-BN coating layer was about 2 nm. On the outside of the h-BN, a Si coating layer with a thickness of about 1 nm was uniformly coated

[0043] (4) Properties of Single-Walled Carbon Nanotube @ h-BN @ Si Composite Film

[0044] The single-walled carbon nanotube @ h-BN @ Si composite film was placed in argon and heated at 1000 °C for 24 h, and its structure remained unchanged, indicating that the composite film has excellent high-temperature resistance. Another composite film prepared under the same conditions was placed in a rapid heating device. Under the protection of high-purity Ar (volume purity > 99.999%), it was heated to 2000 °C at a rate of 200 °C / s and then immediately cooled, and the structure of the composite film remained unchanged. This result proves that the single-walled carbon nanotube @ h-BN @ Si composite film has excellent thermal shock resistance

[0045] Example 3

[0046] In this example, the process for controllably preparing a single-walled carbon nanotube @ Si @ h-BN composite film is as follows

[0047] (1) Preparation of Single-Walled Carbon Nanotube @ Si Composite Film by Magnetron Sputtering

[0048] The preparation of the single-walled carbon nanotube film was the same as in step (1) of Example 1, and the single-walled carbon nanotube film was fixed on the sample stage of the magnetron sputtering. The sample stage was sent into a vacuum environment of 1.3×10 -5 Pa, and the sputtering parameters of the magnetron sputtering were set as follows: the starting power was 10 W, the rotation speed of the sample stage was 10 rad / min, the working pressure of the Ar gas was 4 mTorr, the sputtering power was 10 W, the pre-sputtering time was 300 s, and the sputtering time was 900 s

[0049] (2) Preparation of Single-Walled Carbon Nanotube @ Si @ h-BN Composite Film by Low-Pressure Chemical Vapor Deposition

[0050] The single-walled carbon nanotube @ Si composite film prepared in step (2) of Example 3 was placed in a low-pressure chemical vapor deposition system. Using ammonia borane as the precursor source, when the vacuum degree was 10 -2 Pa, it was grown at 1100 °C for 120 min

[0051] (3) Structural Characterization of Single-Walled Carbon Nanotube@Si@h-BN Composite Film

[0052] The transmittance of the single-walled carbon nanotube@Si@h-BN composite film to visible light at 550 nm was measured to be 89.4%. Then, the prepared single-walled carbon nanotube@Si@h-BN composite film was pressed onto a copper mesh microgrid for transmission electron microscopy observation. The results are as follows Figure 6 shown. The single-walled carbon nanotube bundles were first coated with 1-2 nm of Si, and then coated with 7-8 layers of highly crystalline h-BN outside the Si coating layer. The thickness of the h-BN coating layer was about 2.5 nm, and the interlayer spacing was 0.34 nm, with good layered structure and interface quality.

[0053] (4) Properties of Single-Walled Carbon Nanotube@Si@h-BN Composite Film

[0054] The single-walled carbon nanotube@Si@h-BN composite film was placed in an Ar gas flow of 10000 sccm, and its structure remained unchanged, indicating that the composite film still maintained excellent mechanical properties. The composite film prepared under the same conditions was placed in a plasma cleaning equipment, the power was set to 20 W, hydrogen was used as the plasma source, and it was treated for 60 min under a vacuum of 1×10 -3 Pa. The composite film still maintained a complete self-supporting structure. Transmission electron microscopy observation of its microstructure showed that the carbon nanotube structure was not damaged. This proves that the single-walled carbon nanotube@h-BN@W@h-BN composite film has excellent plasma etching resistance.

[0055] Example 4.

[0056] In the example, the process of controllably preparing the single-walled carbon nanotube@h-BN@Nb composite film is as follows

[0057] (1) Preparation of Single-Walled Carbon Nanotube@h-BN Composite Film by Low-Pressure Chemical Vapor Deposition

[0058] The collection and transfer of the single-walled carbon nanotube film were the same as in step (1) of Example 1. The single-walled carbon nanotube film was placed in a low-pressure chemical vapor deposition system. Using ammonia borane as the precursor source, when the vacuum was 10 -2 Pa, it was grown at 1000 °C for 80 min.

[0059] (2) Preparation of Single-Walled Carbon Nanotube@h-BN@Nb Composite Film by Ion Beam Sputtering

[0060] The single-walled carbon nanotube@h-BN composite film obtained in step (1) of Example 4 was fixed on the sample stage of the ion beam sputtering equipment. The sample was placed in a vacuum of 2.66×10 -4In an ion beam sputtering device of Pa, the sputtering parameters are set as follows: the working voltage is 20 kV, the working current is 0.6 mA, the pre-sputtering time is 200 s, the working time is 1000 s; the Ar gas flow rate is 3.6 mTorr.

[0061] (3) Structural characterization of single-walled carbon nanotube @ h-BN @ Nb composite film

[0062] The transmittance of the single-walled carbon nanotube @ h-BN @ Nb composite film to 550 nm visible light is tested to be 89.9%. Then, the prepared single-walled carbon nanotube @ h-BN @ Nb composite film is pressed onto a copper mesh microgrid for transmission electron microscopy observation. The single-walled carbon nanotube bundles are first coated with 5-6 layers of highly crystalline h-BN. The thickness of the h-BN coating layer is about 2 nm, and the layer spacing is 0.34 nm, having a good layered structure and interface quality. Then, it is coated with 1-2 nm of Nb outside the h-BN coating layer.

[0063] (4) Properties of single-walled carbon nanotube @ h-BN @ Nb composite film

[0064] The single-walled carbon nanotube @ h-BN @ Nb composite film is placed in an argon gas flow with a flow rate of 10000 sccm, and its structure remains unchanged, indicating that the composite film has excellent mechanical properties. Another composite film prepared under the same conditions is placed in a rapid heating device. Under the protection of high-purity Ar (volume purity > 99.999%), it is heated to 2000 °C at a rate of 200 °C / s and then immediately cooled. The structure of the composite film remains unchanged, thus proving that the single-walled carbon nanotube @ h-BN composite film has excellent thermal shock resistance.

[0065] Example 5.

[0066] In the example, the process of controllably preparing carbon nanotube @ h-BN @ W composite film is as follows:

[0067] (1) Preparation of single-walled carbon nanotube @ h-BN composite film by low-pressure chemical vapor deposition

[0068] The collection and transfer of the single-walled carbon nanotube film are the same as in step (1) of Example 1. The single-walled carbon nanotube film is placed in a low-pressure chemical vapor deposition system. Using ammonia borane as the precursor source and the vacuum degree is 10 -2 Pa, grow at 1000 °C for 70 min.

[0069] (2) Preparation of single-walled carbon nanotube @ h-BN @ W composite film by magnetron sputtering

[0070] The single-walled carbon nanotube film in step (1) of Example 5 is fixed on the sample stage of the magnetron sputtering. The sample stage is sent into the magnetron sputtering device at 1.3×10 -5In a Pa vacuum environment, the sputtering parameters of magnetron sputtering are set as follows: the starting power is 15 W, the rotation speed of the sample stage is 10 rad / min, the working pressure of the gas is 5 mTorr, the sputtering power is 10 W, the pre-sputtering time is 800 s, and the sputtering time is 2000 s.

[0071] (3) Structure characterization of single-walled carbon nanotube@h-BN@W composite film

[0072] The visible light transmittance of the single-walled carbon nanotube@h-BN@W composite film at 550 nm is tested to be 89.7%. Then, the prepared single-walled carbon nanotube@h-BN@W composite film is pressed onto a copper mesh microgrid for transmission electron microscopy observation, as Figure 7 shown. The single-walled carbon nanotube bundles are first coated with 4 - 5 layers of highly crystalline h-BN. The thickness of the h-BN coating layer is about 1.5 nm, and the layer spacing is 0.34 nm, having a good layered structure and interface quality. Then, it is coated with 2 - 3 nm of W outside the h-BN coating layer.

[0073] (4) Performance of single-walled carbon nanotube@h-BN@W composite film

[0074] The single-walled carbon nanotube@h-BN@W composite film is placed in a rapid heating device and heated to 2000 °C at a rate of 300 °C / s, and its structure remains unchanged, indicating that the composite film has excellent thermal shock resistance.

[0075] Example 6.

[0076] In this example, the process of controllably preparing carbon nanotube@h-BN@W@h-BN composite film is as follows:

[0077] (1) Preparation of single-walled carbon nanotube@h-BN composite film by low-pressure chemical vapor deposition

[0078] The collection and transfer of the single-walled carbon nanotube film are the same as in step (1) of Example 1.

[0079] (2) Preparation of single-walled carbon nanotube@h-BN@W composite film by magnetron sputtering

[0080] Same as step (2) of Example 5. The difference is that the sputtering parameters of magnetron sputtering become: the working pressure of Ar gas is 3 mTorr, the sputtering power is 2 W, the pre-sputtering time is 1000 s, and the sputtering time is 1500 s.

[0081] (3) Preparation of single-walled carbon nanotube@h-BN@W@h-BN composite film by low-pressure chemical vapor deposition

[0082] The prepared single-walled carbon nanotube@h-BN@W composite film is placed in the low-pressure chemical vapor deposition system again, using ammonia borane as the precursor source, and the vacuum degree is 10-2 At a pressure of Pa, it was grown at 900 °C for 60 min.

[0083] (4) Structural characterization of single-walled carbon nanotube@h-BN@W@h-BN composite film

[0084] The transmittance of the single-walled carbon nanotube@h-BN@W@h-BN composite film to visible light at 550 nm was measured to be 89.1%. Then, the single-walled carbon nanotube@h-BN@W@h-BN composite film was pressed onto a copper mesh microgrid for transmission electron microscopy observation. The composite film formed a sandwich structure. The single-walled carbon nanotube bundles were first coated with 5-6 layers of highly crystalline h-BN. The thickness of the h-BN coating layer was about 2 nm, and the interlayer spacing was 0.34 nm, showing good layered structure and interface quality. Then, the h-BN coating layer was coated with 1-2 nm of W, and there were 3-4 layers of h-BN coating outside the W coating.

[0085] (5) Properties of single-walled carbon nanotube@h-BN@W@h-BN composite film

[0086] The single-walled carbon nanotube@h-BN@W composite film was heated in air at 600 °C for 24 h, and its structure remained unchanged, indicating that the composite film has excellent high-temperature oxidation resistance. When heated to 2300 °C at a rate of 500 °C / s, its structure remained unchanged, indicating that the composite film has excellent thermal shock resistance. Another composite film prepared under the same conditions was placed in a plasma cleaning device. The power was set to 10 W, and hydrogen was used as the plasma source. It was treated at 1×10 -3 Pa (vacuum degree) for 180 min. The composite film still maintained a complete self-supporting structure. Transmission electron microscopy observation of its microstructure showed that the carbon nanotube structure was not damaged. This proves that the single-walled carbon nanotube@h-BN@W@h-BN composite film has excellent plasma etching resistance.

[0087] The implementation results show that the composite film prepared by the method of the present invention has strong interfacial bonding, improves the chemical stability of the carbon nanotube film, and can broaden the application scenarios of carbon nanotubes to extreme service environments such as high-concentration atomic oxygen / hydrogen, high-concentration plasma, strong light irradiation, high-temperature oxygen-containing, and strong air flow impact.

[0088] The design concept and implementation scheme of the present invention have been specifically described above. However, based on the present invention, some modifications and improvements can still be made. These modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection required by the present invention.

Claims

1. A method for preparing a carbon nanotube composite film for use under extreme conditions, characterized in that: A self-supporting film with a thickness of 10 to 200 nm formed by overlapping a carbon nanotube network is used as a substrate. First, a non-metallic coating layer with a thickness of 0.3 to 10 nm and containing at least two elements of B, C, N, O, P, Si, Ge, As and Sb is heteroepitaxially grown on the carbon nanotubes and their bundles by normal pressure or vacuum chemical deposition. Then, a metal / alloy or metal compound containing at least one of the elements Bi, Ti, Al, Zr, Mo, W, Ru, Nb, Hf, Re and Rh is controllably deposited on the carbon nanotubes and their bundles by a physical deposition method. The composite film has excellent airflow impact resistance, atomic hydrogen / oxygen resistance, hydrogen / oxygen plasma resistance, heat shock resistance, high-temperature oxidation-reduction resistance and acid and alkali corrosion resistance while maintaining light transmission and flexibility.

2. The method for preparing a carbon nanotube composite film for use under extreme conditions according to claim 1, characterized in that: In order to improve the thermal shock resistance of the composite film, after depositing the non-metallic coating layer, a metal / alloy or metal compound of at least one of the elements Bi, Ti, Al, Zr, Mo, W, Ru, Nb, Hf, Re, and Rh is controllably coated by a controllable physical deposition method, and the metal compound is a metal silicide, a metal nitride, or a metal carbide.

3. The method for preparing a carbon nanotube composite film for use under extreme conditions according to claim 1, characterized in that: In order to improve the composite film's resistance to plasma, atomic hydrogen / oxygen or acid and alkali corrosion, the outermost layer of the composite film is h-BN or a metal compound.

4. The method for preparing a carbon nanotube composite film for use under extreme conditions according to claim 1, characterized in that: In order to improve the high temperature oxidation-reduction resistance of the composite film, the outermost layer of the composite film is h-BN, diamond, c-BN, Si3N4 or SiC ceramic material.

5. The method for preparing a carbon nanotube composite film for use under extreme conditions according to claim 1, characterized in that: In order to maintain the light transmittance and mechanical properties of the composite film, the total thickness of the non-metallic coating layer needs to be less than 10nm; when depositing the coating metal, alloy or metal compound, a physical deposition method such as atomic layer deposition, magnetron sputtering, ion beam sputtering or thermal evaporation is used, which has a high controllable coating thickness, and the deposition thickness is 1 to 5nm.

6. The method for preparing a carbon nanotube composite film for use under extreme conditions according to any one of claims 1 to 5, characterized in that: When the composite film is composed of a single single-walled carbon nanotube, its innermost coating layer should be h-BN, c-BN or B4C with high crystallinity and high chemical stability, and have good layered structure and interface quality.

7. The method for preparing a carbon nanotube composite film for use under extreme conditions according to claim 1, characterized in that: This method significantly improves the chemical stability of carbon nanotube films, and expands the application scenarios of carbon nanotubes to extreme service environments such as high-concentration atomic oxygen / hydrogen, high-concentration plasma, strong light irradiation, high-temperature oxygen / hydrogen, high-concentration acid and alkali, strong airflow impact, or rapid temperature rise and fall.